منهج الامام المنذري في توظيف احاديث الترغيب والترهيب تربويا : دراسة حديثية نقدية - عباس, تاج الدين أحمد سعيد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study intends to identify the significance of weak hadith (Hadith Al-dhaif) in the books of previous Muslim scholars as they deduced it based on certain rules which are known to them. One of them is Imam al Mundhiri who was very well-versed in the science of hadith and a prominent scholar of his time. The study also attempts to identify the methodology used by Imam al Mundhiri in his book titled Al-Targheeb wal-Tarheeb, especially in dealing with 2,052 weak hadith. In order to achieve this, the study attempts to answer the following questions: Is it permissible to use any type of weak hadith? Did the first generation of scholars of hadith differentiate between weak and very weak hadith in terms of deducing them especially in matters involving exhorting and warning? Is there any difference between very weak hadith and fabricated ones as defined by early and modern generations of scholars? Why did Imam al Mundhiri mention one fabricated hadith in his book in spite of it being a rejected hadith based on the consensus of scholars? The study has come up with several important results which indicate that the first generation of hadith scholars relied on weak hadith in deciding on rulings in the absence of authentic hadith, particularly in the case of exhorting and warning. This is the standard viewpoint of the majority of scholars, if not the viewpoint of all; therefore, those who attempt to disqualify the weak hadith in general have no evidence, and we should not pay any serious attention to their views. Those that have differed, their differences were just based on the issue of criticism and justification which depended upon lenient, moderate and strict approaches, consequently, it had left a very huge impact on the degree of the weakness of hadith, differing from minor to major. By taking the above situation into consideration, the study concludes that there is no harm in making inferences from weak hadith even if it is an isolated case; however, it should be classified according to the preferred conditions of acceptance of hadith, hence, the definition of hadith al dhaif should be verified terminologically which not only denotes comprehensiveness of this term, but also gives due rights to the statements of the scholars in view of their unanimity.